2020
DOI: 10.1002/ardp.202000143
|View full text |Cite
|
Sign up to set email alerts
|

Indole/isatin‐containing hybrids as potential antibacterial agents

Abstract: The emergence and worldwide spread of drug-resistant bacteria have already posed a serious threat to human life, creating the urgent need to develop potent and novel antibacterial drug candidates with high efficacy. Indole and isatin (indole-2,3-dione) present a wide structural and mechanistic diversity, so their derivatives possess various pharmacological properties and occupy a salient place in the development of new drugs. Indole/isatin-containing hybrids, which demonstrate a promising activity against a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 197 publications
(149 reference statements)
0
15
0
Order By: Relevance
“…IR spectra were measured with a Bruker Vector-22 instrument for the samples in KBr pellets. 1 H and 13 C NMR spectra were recorded on a Bruker Avance-400 or Bruker Avance-600 Bruker spectrometers at 400, 600 and 100.6, 150 MHz, respectively. Chemical shifts were reported in ppm relative to residual signals of deuterated solvents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR spectra were measured with a Bruker Vector-22 instrument for the samples in KBr pellets. 1 H and 13 C NMR spectra were recorded on a Bruker Avance-400 or Bruker Avance-600 Bruker spectrometers at 400, 600 and 100.6, 150 MHz, respectively. Chemical shifts were reported in ppm relative to residual signals of deuterated solvents.…”
Section: Methodsmentioning
confidence: 99%
“…The progressing number of works on synthetic procedures [3] and the studies of this heterocycle push researchers in this area to publish generalized data on one or another type of biological activity [4][5][6][7]. It is due to the manifestation of isatin and its derivatives of a wide spectrum of activity, such as anti-cancer [8][9][10], anti-tubercular [11,12], antibacterial [13], anti-COVID [14,15], fungicidal [16,17], etc (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Indole derivatives with fascinating structural and mechanistic diversity are potential inhibitors of bacterial pyruvate kinase, GTPase, FtsZ, efflux pump, DNA gyrase, and topoisomerase IV, revealing the potential of indole derivatives for fighting against various bacteria, even hard‐to‐treat pathogens including MRSA. [ 47,48 ] Accordingly, 1,2,4‐triazole–indole hybrids are potential prototypes for the discovery of novel anti‐MRSA candidates.…”
Section: 24‐triazole–indole Hybridsmentioning
confidence: 99%
“…The mechanistic study demonstrated that indole derivatives could exhibit the antibacterial activity through diverse mechanisms, including the inhibition of bacterial pyruvate kinase (PK), GTPase, filamentous temperature‐sensitive protein Z (FtsZ), efflux pump, DNA gyrase, and topoisomerase IV; thus, these derivatives possess a potential activity against a panel of clinically important drug‐sensitive and drug‐resistant, and even multidrug‐resistant pathogens including MRSA. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic study demonstrated that indole derivatives could exhibit the antibacterial activity through diverse mechanisms, including the inhibition of bacterial pyruvate kinase (PK), GTPase, filamentous temperature-sensitive protein Z (FtsZ), efflux pump, DNA gyrase, and topoisomerase IV; thus, these derivatives possess a potential activity against a panel of clinically important drug-sensitive and drug-resistant, and even multidrugresistant pathogens including MRSA. [19,20] Dimerization and hybridization are promising strategies to circumvent multidrug resistance, improve the efficacy, reduce the side effects, and improve pharmacokinetic, pharmacodynamic, as well as physicochemical profiles. [21,22] In recent decades, diverse indole dimers and hybrids ( Figure 1…”
mentioning
confidence: 99%